Infants' numerical abilities and models of early enumeration - Nikoloska, Ana (Array, 2008)
Summary: The early studies of infants' numerical abilities have shown that infants could discriminate numerosities and even form expectation about the outcome of a mathematical operation. In these studies, however, the number was confounded with continuous variables that co-vary with number, therefore subjecting this early research to a criticism. So, it was not clear whether infants possess genuine numerical abilities or not. In recent studies a control for continuous variables was introduced and it has been found that infants discriminate large numerosities, but not small ones. When small numerosities are confounded with other variables, infants discriminate them easily. It appears that infants represent small and large numerosities differently. Two systems of number have been proposed to account for the findings. One of the systems is responsible for approximate representation of large numerical magnitudes and the other for precise representation of small ones. Several mechanisms have been proposed to explain how these systems work. The systems are found across animals as well and could provide a foundation upon which more sophisticated, specifically human, mathematical abilities are built.